2023
DOI: 10.29173/wclawr82
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patterns Across the Six Canonical Factors Underlying Wrongful Convictions

Abstract: Research has established six “canonical” factors underlying wrongful convictions including: mistaken witness identification (MWID), false confession (FC), perjury or false accusation (P/FA), false or misleading forensic evidence (F/MFE), official misconduct (OM), and inadequate legal defense (ILD). While we know these factors do not occur in isolation, researchers have yet to examine the patterns across these six factors. In the present article, we apply latent class analysis to explore how these six factors m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
4
9
0
Order By: Relevance
“…This was done using two methods: the Berube et al ( 2023) latent class analysis (LCA) method and decision trees. Using the LCA method, they found that a fourclass model provided the best statistical fit, corroborating Berube et al (2023) while using a larger data set. The four predicted classes are as follows: intentional errors, witness mistakes, investigative corruption, and failures to investigate.…”
supporting
confidence: 52%
“…This was done using two methods: the Berube et al ( 2023) latent class analysis (LCA) method and decision trees. Using the LCA method, they found that a fourclass model provided the best statistical fit, corroborating Berube et al (2023) while using a larger data set. The four predicted classes are as follows: intentional errors, witness mistakes, investigative corruption, and failures to investigate.…”
supporting
confidence: 52%
“…Scholars have extensively examined wrongful conviction cases (e.g., Garrett, 2011;Gross, 2005Gross, , 2017Zalman, 2010Zalman, /2011Zalman & Larson, 2015/2016Wells & Leo, 2008) and the factors contributing to these errors, such as faulty eyewitness identifications or false confessions (e.g., Kassin et al, 2010;Wells et al, 1998;Wells & Leo, 2008). They identified six "canonical factors" contributing to these injustices, including mistaken witness identification, perjury or false accusations, false confessions, false or misleading forensic evidence, official misconduct, and inadequate legal defense (Berube et al, 2022). Researchers have also explored factors such as psychological influences on eyewitnesses, informants/snitches, cognitive biases among experts and jury members, judicial processes like plea bargaining and trials, and forensic science errors (Covy, 2013;Gould & Leo, 2010;Henry, 2020;Stinson et al, 1997;Wells & Quinlivan, 2009;Wells et al, 1998;Wells & Leo, 2008).…”
Section: Previous Researchmentioning
confidence: 99%
“…Wrongful convictions can stem from various factors, with the primary contributing factors encompassing perjury or false accusations, mistaken identifications by victims and witnesses, misapplication of forensic science, false confessions, and professional misconduct (Innocence Project, 2023b; National Registry of Exonerations, 2023b). While a singular factor may account for errors in a particular case, more frequently, it is a combination of factors that leads to a wrongful conviction (Berube, et al 2022;Yaroshefsky & Schaefer, 2014).…”
Section: Factors Contributing To Wrongful Convictionsmentioning
confidence: 99%